2008
DOI: 10.1590/s0101-20612008000400016
|View full text |Cite
|
Sign up to set email alerts
|

Extração, secagem e torrefação da amêndoa do pequi (Caryocar brasiliense Camb.)

Abstract: IntroduçãoO pequi (Caryocar brasiliense Camb.) é uma planta arbó-rea que engloba cerca de 20 espécies, a maioria de porte alto, compondo a vegetação da floresta amazônica e estendendo seu habitat natural aos países limítrofes, principalmente, Peru, Suriname e Guianas. No Brasil, o pequi distribui-se desde o Pará e o Amazonas, sua área de maior ocorrência, aos Estados do Nordeste e, ainda, aos Estados do Mato Grosso do Sul, Goiás, Minas Gerais, São Paulo e norte do Paraná. É uma planta típica de cerrado e das c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
1
4
0
3
Order By: Relevance
“…Pequi almond obtained a moisture content of 5.89%. In their work, Rabêlo et al (2008) found a moisture content of 5.26% for toasted pequi almond, similar to the value found in the present study. The low moisture content of pequi almond contributed to a decrease in the humidity of the almond cereal bars in the formulation, since formulation A (12.5% pequi almond) and formulation B (25% pequi almond) presented a moisture content of 6.7% differing significantly from the standard formulation, which obtained 9.16% moisture.…”
Section: Resultssupporting
confidence: 91%
“…Pequi almond obtained a moisture content of 5.89%. In their work, Rabêlo et al (2008) found a moisture content of 5.26% for toasted pequi almond, similar to the value found in the present study. The low moisture content of pequi almond contributed to a decrease in the humidity of the almond cereal bars in the formulation, since formulation A (12.5% pequi almond) and formulation B (25% pequi almond) presented a moisture content of 6.7% differing significantly from the standard formulation, which obtained 9.16% moisture.…”
Section: Resultssupporting
confidence: 91%
“…The baru and pequi almonds and the cerrado cashew nut were roasted to inactivate the possible anti-nutritional factors (Togashi & Sgarbieri, 1994) and to investigate the nutritional quality of the almonds and of the nut as usually consumed. The baru almond and the peanuts were roasted at 140°C for 30 min (Fernandes et al, 2010) and the pequi almond and cerrado cashew nut at 130°C for 30 min (Rabêlo, Torres, Geraldine, & Silveira, 2008) in an electric oven. Thereafter, the almonds and the nut were milled with a blender and sieved through a 60-mesh for chemical analysis and for use in the experimental diets.…”
Section: Sample Preparation Proceduresmentioning
confidence: 99%
“…Oil can be extracted from pequi almonds, have about 50%, and used as a source of protein, have about 20% (SOUSA et al, 2011). RABÊLO et al (2008), used techniques for the extraction, drying, and roasting of the pequi almond, to analyze and evaluate the preferences and better acceptance concerning the roasting time of the almonds. The authors emphasized that almonds roasted in 30 minutes at 130 ºC showed better acceptance and had better sensory characteristics of color and texture.…”
Section: Introductionmentioning
confidence: 99%